2013 IEEE 31st VLSI Test Symposium (VTS) 2013
DOI: 10.1109/vts.2013.6548929
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of gate oxide short in FinFETs and the test methods for FinFET SRAMs

Abstract: When CMOS technologies enter nanometer scale, FinFET has become one of the most promising devices because of the superior electrical characteristics. Nonetheless, due to the scaling of dielectric thickness and the occurring of line-edge roughness, FinFETs may suffer the gate oxide short. Gate oxide short is a defect that has been widely discussed in planar bulk MOSFETs. But for FinFETs, the defect characteristics have not been studied yet. In this paper, we investigate the fault behaviors of the gate oxide sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Moreover, GOS causes a weak inversion and tightens the channel for carriers, leads to a slight increase of V T h (ΔV T h = 170mV ). The negative ID when the VDD = low, which happens in bulk CMOS and FinFET [25,16] , is observed here when the remaining gates of the transistor allow carriers to pass through the channel. For example, for faulty n-type devices used in SP logic gates, polarity controls constantly permit electrons to pass through channel, and therefore negative ID exists when the VD decreases.…”
Section: B Tig-sinwfet Performance In Presence Of Gosmentioning
confidence: 73%
See 2 more Smart Citations
“…Moreover, GOS causes a weak inversion and tightens the channel for carriers, leads to a slight increase of V T h (ΔV T h = 170mV ). The negative ID when the VDD = low, which happens in bulk CMOS and FinFET [25,16] , is observed here when the remaining gates of the transistor allow carriers to pass through the channel. For example, for faulty n-type devices used in SP logic gates, polarity controls constantly permit electrons to pass through channel, and therefore negative ID exists when the VD decreases.…”
Section: B Tig-sinwfet Performance In Presence Of Gosmentioning
confidence: 73%
“…The authors in [12,13] investigated open and short faults on FinFETs, and they showed that Stuck-at Open Faults (SOFs) on the back gate of FinFET have a unique effect on the leakage and delay. In [16], the GOS defect on the Fin-FET dielectric have been studied . The amount of Saturation Drain Current (I D(SAT ) ) vastly increases with GOS at the front gate dielectric.…”
Section: Background and Motivationmentioning
confidence: 99%
See 1 more Smart Citation
“…Lin et al [17] investigated the efficacy of using March Tests as well as I DDQ to detect Gate Oxide Shorts (GOS) in FinFET SRAMs. According to the authors, this type of defects causes more complex fault behaviours in FinFETs than in planar transistors due to their unique structure.…”
Section: Finfet Testingmentioning
confidence: 99%
“…Using exhaustive March tests to sensitize faults results in expensive manufacturing tests, as the test cost is directly related to the time each product stays on the tester [13]. Disparate approaches, such as monitoring the static or dynamic current consumption of SRAM cells [14][15][16][17], have been proposed to improve the detection of weak defects. Nevertheless, their efficacy regarding FinFET devices affected by resistive defects is unknown.…”
Section: Introductionmentioning
confidence: 99%